The Re-emergence of the Residual Income Model in the Valuation of Firms and Investment Projects - Cziglerné Erb, Edina (Public Finance Quarterly, 2020)
Residual income valuation was already known and used in valuation theory and practice previously, however, the method has been subject to increasing attention in the past decades. By comparing the discounted cash flow method and the residual income model, this paper seeks to answer the question of what practical implications the difference in theory results in. The discounted cash flow method continues to be widely popular in literature and international practice, however, it may give rise to flawed results in certain cases. With the help of specific business examples, the study highlights that in such cases, the risks of under or overestimation can be mitigated with the help of the RIM model. The largest benefit of the residual income model compared to the DCF method is that instead of deriving the value solely from the future, it gives a central role to the already known book value, and the speculative value – determined based on the accounting income – plays a less significant role in the course of valuation.